Interim therapeutic restoration approach versus treatment under general anaesthesia approach. Issue 6 (5th March 2017) - Lim, Songping Nicholas; Kiang, Leroy; Manohara, Ranjan; Tong, Huei Jinn; Nair, Rahul; Hong, Catherine; Hu, Shijia
Abstract : Background: Although dental treatment under general anaesthesia (GA) remains the long‐established approach for treating anxious children, treatment under GA presents with increased risks, costs and parental acceptability issues. Interim therapeutic restoration (ITR) has been proposed as an alternative approach. Aim: To compare the incidence and types of failures between children managed with the ITR approach and those managed under GA within 12 months of treatment completion. Design: A retrospective cohort study of children who received dental treatment utilizing the ITR approach was compared to children treated under GA. Age, gender and dental disease matching was done. Statistical analyses were carried out with Independent t‐test and chi‐square analyses. Results: A total of 132 children (GA = 66, ITR = 66) were included, and the groups did not differ in terms of initial age, sex, dmft and initial behaviour score. ITR group had a significantly higher rate ( P < 0.001; 95% CI: [0.21 to 0.97]) of restorative failure and visits required when compared to the GA group. There were no difference for incidence of pain ( P = 0.55; 95% CI: [−0.074 to 0.10]) and behaviour scores ( P = 0.46) between the two groups at the 12‐month visit. Conclusions: ITR approach may be a viable alternative to the GA approach when treating paediatric dental patients.